TRADISI OGOH-OGOH DI BALI DALAM TINJAUAN KRITIS FILSAFAT KEBUDAYAAN CORNELIS ANTHONIE VAN PEURSEN - Gede Agus Siswadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This article seeks to explore the ogoh-ogoh tradition in Bali. Ogoh-ogoh which is the result of the artistic expression of the Balinese people who are always experiencing dynamics of change and development. The ogoh-ogoh tradition in Bali is developing according to the times. The ogoh-ogoh tradition in Bali when viewed critically with the cultural philosophy of Cornelis Anthonie Van Peursen by paying attention to the stages of cultural development in the mythical stage, ontological stage and functional stage. Ogoh-ogoh historically, mythology appears as a symbol and embodiment of bhuta kala which is disturbing human life, so that the energies of bhuta kala (negative energy) are always harmonized and neutralized into the powers of the gods (positive energy). Thenext development of the bhuta kala myth developed by breaking away from the shackles of myth to an ontological understanding, and finally at the functional stage as a show (parade) for cultural tourism.